2007
DOI: 10.1037/0735-7028.38.3.259
|View full text |Cite
|
Sign up to set email alerts
|

Transformational supervision: When supervisors mentor.

Abstract: Can a psychologist simultaneously fill the roles of clinical supervisor and mentor to a trainee? What are the implications of adding a mentoring component to a supervisory relationship? Like academic advising, supervision need not incorporate a mentoring function. However, the author hypothesizes that, all things considered, it is better for supervisees, and probably supervisors and training sites, too, when supervising psychologists engage supervisees in connected, collaborative, and increasingly reciprocal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 60 publications
2
98
1
Order By: Relevance
“…A possible consequence is that failing students are passed, despite concern about their performance. Similar concerns are found in other disciplines, for example, occupational therapy (Ilot and Murphy, 1997), nursing (Lankshear, 1990;Duffy, 2004), teaching (Knowles et al, 1995), and counselling psychology (Vacha-Haase et al, 2004;Hoffman et al, 2005;Johnson, 2007).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…A possible consequence is that failing students are passed, despite concern about their performance. Similar concerns are found in other disciplines, for example, occupational therapy (Ilot and Murphy, 1997), nursing (Lankshear, 1990;Duffy, 2004), teaching (Knowles et al, 1995), and counselling psychology (Vacha-Haase et al, 2004;Hoffman et al, 2005;Johnson, 2007).…”
Section: Introductionmentioning
confidence: 96%
“…The nursing literature explored the challenges in failing students on clinical placements (Lankshear, 1990;Duffy, 2004). Teaching (Knowles et al, 1995), occupational therapy (Ilott and Murphy, 1997) and counselling psychology (Vacha-Haase et al, 2004;Hoffman et al, 2005;Johnson, 2007;) revealed similar concerns around difficulties in failing students on placement. Indeed, the term 'failure to fail' (Duffy, 2004;Shapton, 2006) emerges in a number of professional contexts.…”
Section: Literature Review Of Placement Failurementioning
confidence: 99%
“…(Warren, 2005) and lose his or her ability to provide unbiased evaluation (Johnson, 2007;Welfel, 2002) and serve as a gatekeeper for the profession (Welfel, 2002). Nevertheless, avoiding dual roles is not practical in academe (Borders & Brown, 2005;Warren, 2005;Welfel, 2002).…”
Section: Multiple Rolesmentioning
confidence: 99%
“…Assessment of the overall functions of mentoring might assist with the comprehensive needs of mentees being met. The Mentor Function Scale (Tepper et al, 1996) has been used in adapted forms in the field of counselor education by various researchers (e.g., Black, 1998;Farrell, 2007).A major focus of mentoring is centered on psychosocial and career development (Farrell, 2007;Johnson, 2007;Kram, 1983). Mentoring relationships evolve over time; therefore, the psychosocial aspect of the mentoring relationship develops after trust has been established.…”
mentioning
confidence: 99%
“…Engineering leadership is becoming more of a common curricular priority at the undergraduate level, as engineering industry seeks engineering graduates that have leadership skills and experiences; however, not much curricular emphasis is placed on developing leadership skills through graduate school or for junior faculty members. Recent studies have linked transformational leadership 5,6 -the leadership style that seeks to help each individual member of a team develop her or his maximum talent and potential-to innovation success, 27 learning outcomes, and higher productivity. 28 By adopting a "transformational leadership" approach to leading and sculpting a research group, advisors can help students plan their own success.…”
Section: Theories Of Leadershipmentioning
confidence: 99%